Grafting Neural Stem and Progenitor Cells Into the Hippocampus of Juvenile, Irradiated Mice Normalizes Behavior Deficits - Sato, Yoshiaki; Shinjyo, Noriko; Sato, Machiko; Nilsson, Marie K. L.; Osato, Kazuhiro; Zhu, Changlian; Pekna, Marcela; Kuhn, Hans G.; Blomgren, Klas (Frontiers in Neurology, 2018)
The pool of neural stem and progenitor cells (NSPCs) in the dentate gyrus of the hippocampus is reduced by ionizing radiation. This explains, at least partly, the learning deficits observed in patients after radiotherapy, particularly in pediatric cases. An 8 Gy single irradiation dose was delivered to the whole brains of postnatal day 9 (P9) C57BL/6 mice, and BrdU-labeled, syngeneic NSPCs (1.0 × 105 cells/injection) were grafted into each hippocampus on P21. Three months later, behavior tests were performed. Irradiation impaired novelty-induced exploration, place learning, reversal learning, and sugar preference, and it altered the movement pattern. Grafting of NSPCs ameliorated or even normalized the observed deficits. Less than 4% of grafted cells survived and were found in the dentate gyrus 5 months later. The irradiation-induced loss of endogenous, undifferentiated NSPCs in the dentate gyrus was completely restored by grafted NSPCs in the dorsal, but not the ventral, blade. The grafted NSPCs did not exert appreciable effects on the endogenous NSPCs; however, more than half of the grafted NSPCs differentiated. These results point to novel strategies aimed at ameliorating the debilitating late effects of cranial radiotherapy, particularly in children.